Structure and tectonic evolution of the South Patagonian fold and thrust belt: pairing between subduction dynamics, climate and tectonic deformation - Ghiglione, Matias (2018)
We present an appraisal of structural domains in the SPA (Southern Patagonian Andes) between 46° and 52°S, recognizing a thickskinnedBD (Basement domain) and a hybrid thick- and thin-skinned systems in the FTB (fold and thrust belt).Two major structural segments can be clearly defined north and south of 48°30´: (1) Northern segment: With a steady orogenicwidth of around 340-360km, is characterized by a well-developed basement domain, and a narrow FTB. The inner domain of theFTB is very narrow.The comparison of our geometrical data with exhumation patterns from thermochronological studies evidences importantcorrelations: (1) The wide basement in the northern sector coincides with exhumation ages younger than 3 Ma throughout thisdomain. It has been proposed that this sector was dominated by highly efficient alpine glacial erosion, producing this characteristicyoung exhumation pattern (Thomson 2010). In terms of the critical wedge theory, enhanced erosive exhumation in the highlandof the retro wedge produces active tectonic uplift of the basement domain; while the basement is constantly subdued under thecritical angle, the thrust front does not advance, and the FTB is underdeveloped, in agreement with our empirical observations. (2)The abrupt and steady increase in width and shortening of the FTB towards the southern sector coincides with older basementcooling ages which indicate much reduced late Cenozoic erosion despite dominantly glacial conditions here since the latestMiocene (Thomson et al., 2010). Although orogen width does seem to be around 25% wider between 48°30´and 50°SL, it showsa gradual decline towards the south. Older exhumation ages in the Basement domain coincides with a thicker sedimentary coverand erosion focused in the retroarc, as expected by the critical wedge theory, predicting the development of a wider FTB.